COMPARISON OF PROLENE AND VICRYL SUTURES IN EMERGENCY LAPAROTOMY CLOSURE: A RANDOMIZED CONTROLLED TRIAL (The Research of Medical Science Review, 2025)
Acute abdomen can lead to complications such as electrolyte imbalance, septicemia, anemia, and dehydration, increasing morbidity and mortality if left untreated. Surgical intervention, typically via emergency laparotomy, is often required in conditions like intestinal obstruction, gut perforation, peptic ulcer perforation, and abdominal trauma. A major postoperative complication of laparotomy is burst abdomen, closely linked to the technique and material used for abdominal closure. Although various studies have assessed closure techniques, limited data is available comparing Prolene and Vicryl sutures in our population. The aim of current study is to compare the frequency of burst abdomen using Prolene versus Vicryl sutures for emergency laparotomy closure. This randomized controlled trial was conducted at the Department of General Surgery, Lady Reading Hospital,Peshawar,from03122019to03062020.Atotalof 262 patients undergoing emergency laparotomy were randomly assigned to two groups: Group A received abdominal closure with Prolene, and Group B with Vicryl. Patients were followed until the 15th postoperative day to assess the incidence of burst abdomen.ThemeanageintheProlenegroupwas39.7 ± 8.5 years, and in the Vicryl group, 41.4 ± 9.6 years. Demographics and operative variables were comparable. Burst abdomen occurred in 7.6% of the Prolene group and 28.2% of the Vicryl group (p < 0.001), showing a statistically significant difference. The findings revealed that prolene sutures significantly reduce the incidence of burst abdomen compared to Vicryl in emergency laparotomy closure. Further large-scale RCTs are recommended to confirm these findings.